Synthesis and biological evaluation of novel N-α-haloacylated homoserine lactones as quorum sensing modulators - Syrpas, Michail; Ruysbergh, Ewout; Stevens, Christian V.; De Kimpe, Norbert; Mangelinckx, Sven (Beilstein Journal of Organic Chemistry, 2014)
Novel N-α-haloacylated homoserine lactones, in which a halogen atom was introduced at the α-position of the carbonyl function of the N-acyl chain, have been studied as quorum sensing (QS) modulators and compared with a library of natural N-acylated homoserine lactones (AHLs). The series of novel analogues consists of α-chloro, α-bromo and α-iodo AHL analogues. Furthermore, the biological QS activity of the synthetic AHL analogues compared to the natural AHLs was evaluated. Halogenated analogues demonstrated a reduced activity in the Escherichia coli JB523 bioassay, with the α-iodo lactones being the less active ones and the α-chloro AHLs the most potent QS agonists. Most of the α-haloacylated analogues did not exhibit a significant reduction when tested in the QS inhibition test. Therefore, these novel analogues could be utilized as chemical probes for QS structure–activity studies.
Keywords: halogenated fatty acids; halogenation; N-acylated homoserine lactones; N-α-haloacylated homoserine lactones; quorum sensing